Frugal innovation and sustainability outcomes: findings from a systematic literature review. Issue 6 (16th September 2022) - De Marchi, Valentina; Pineda-Escobar, Maria A.; Howell, Rachel; Verheij, Michelle; Knorringa, Peter
Abstract : Purpose: Advance the state-of-the-art on how frugal innovation links to sustainability outcomes and based on content analysis of empirical publications in the field of frugal innovation, analyzing when and how FI is connected with social, environmental and economic outcomes. Design/methodology/approach: Quantitative content analysis on empirical papers published on frugal innovation, using data visualization techniques to disclose relationships among the constructs adopted. Materials were collected following a step-wise methodology. In total, 130 articles were identified, read in depth and coded according to five main categories: context; development; implementation, adoption, diffusion; characteristics; and impacts. Findings: The potential of frugal innovation to drive sustainability outcomes is influenced by the type of actors developing the innovation, regarding their organizational form (large firms, small firms, non-firm actors), their geographical origin (foreign or local) or motivations (mostly profit-motivated or socially-oriented). Collaboration plays a key role along the various stages of the frugal innovation cycle and is thus relevant for its potential to drive sustainability outcomes. The results reaffirm the need for greater attention to where and when sustainability-enhancing outcomes of frugal innovation are more likely to occur. Originality/value: This study provides a qualitative study based on content analysis of empirical studies to explore the associations between frugal innovations and improved economic, environmental and social sustainability outcomes. The key novelty of this study lies in the systematic coding of each paper regarding the features of the innovation, the innovators, and the outcomes achieved. This allows taking stock of the evidence emerging in such a scattered literature, quantifying the extent to which insights take place in the empirical literature, looking for correlations, and highlight research gaps to understand to what extent frugal innovation can contribute to sustainable development.